Substance abuse treatment processes and outcomes in day/outpatient health maintenance organization setting - McNeese-Smith, Donna K; Faivre, Clare L; Grauvogl, Cynthia; Warda, Nipa Umme Shefa; Kurzbard, Marc A (Journal of addictions nursing, 2014)
Previous research has determined that substance abuse treatment (SAT) is effective under managed care within residential treatment and outpatient treatment, but we have not followed patients after treatment completion. This study examined SAT in both an intensive day treatment and an outpatient treatment program in a large health maintenance organization, with mandatory 12-step participation. We conducted interviews (N = 72) at the beginning, upon completion, and 6 months after completion of treatment. Variables measured were substance use, quality of life, symptoms, functionality, and patient satisfaction as well as Drug Abuse Treatment and Assessment Resources (DATAR) score and treatment completion. Before treatment, DATAR scores were high: 7.68 on a scale of 1-9, indicating serious addictions. Patients showed significant improvement in all variables measured, upon completion of SAT, and additional improvement again 6 months later. Eighty-three percent of subjects completed treatment. Unique advantages of treatment in this setting were discussed, as well as the importance of referral and support from nurses and other healthcare professionals.